The structure of the nucleoprotein binding domain of lyssavirus phosphoprotein reveals a structural relationship between the N-RNA binding domains of Rhabdoviridae and Paramyxoviridae. - Delmas, O; Assenberg, R; Grimes, J; Bourhy, H (2010)
The phosphoprotein P of non-segmented negative-sense RNA viruses is an essential component of the replication and transcription complex and acts as a co-factor for the viral RNA-dependent RNA polymerase. P recruits the viral polymerase to the nucleoprotein-bound viral RNA (N-RNA) via an interaction between its C-terminal domain and the N-RNA complex. We have obtained the structure of the C-terminal domain of P of Mokola virus (MOKV), a lyssavirus that belongs to the Rhabdoviridae family and mapped at the amino acid level the crucial positions involved in interaction with N and in the formation of the viral replication complex. Comparison of the N-RNA binding domains of P solved to date suggests that the N-RNA binding domains are structurally conserved among paramyxoviruses and rhabdoviruses in spite of low sequence conservation. We also review the numerous other functions of this domain and more generally of the phosphoprotein.